Borrelia Lineages Adjacent to Zoonotic Clades in Black Flying Foxes (Pteropus alecto), Australia, 2018–2020 - Taylor B. Verrett; Caylee A. Falvo; Evelyn Benson; Devin N. Jones-Slobodian; Daniel E. Crowley; Adrienne S. Dale; Tamika J. Lunn; Manuel Ruiz-Aravena; Agnieszka Rynda-Apple; Clifton D. McKee; Kerry L. Clark; Alexander W. Gofton; et al. (Emerging Infectious Diseases)
We explored the role of black flying foxes (Pteropus alecto) in Australia as reservoirs of Borrelia bacteria. We found bats infected with 2 Borrelia haplotypes phylogenetically distinct from Lyme or relapsing fever clades. Efforts to sample black flying foxes and their ectoparasites are needed to evaluate zoonotic potential of those Borrelia lineages.